Adhesive performance of dentin bonding agents applied in vivo and in vitro. Effect of intrapulpal pressure and dentin depth - Hebling, Josimeri; Castro, Fabricio L. A.; Costa, Carlos A. S. (Wiley-Blackwell, 2007)
The purpose of this study was to evaluate the influence of intrapulpal pressure and dentin depth on bond strengths of an etch-and-rinse and a self-etching bonding agent to dentin in vitro and in vivo. Twenty-four pairs of premolars were randomly divided into four groups (n = 6) according to the dentin bonding agent, Single Bond and Clearfil SE Bond, and intrapulpal pressure, null or positive. Each tooth of the pair was further designated to be treated in vivo or in vitro. The intrapulpal pressure was controlled in vivo by the delivery of local anesthetics containing or not a vasoconstrictor, while in vitro, it was achieved by keeping the teeth under hydrostatic pressure. Class I cavities were prepared and the dentin bonding agents were applied followed by incremental resin restoration. For the teeth treated in vitro, the same restorative procedures were performed after a 6 month-storage period. Beams with I mm 2 cross-sectional area were prepared and, microtensile tested. Clearfil SE Bond was not influenced by any of the variables of the study, while bond strengths produced in vitro were significatly higher for Single Bond. Overall, lower bond strengths were produced in deep dentin, which reached statistical significance when Single Bond was applied under physiological or simulated intrapulpal pressure. In conclusion, in vitro bonding may overestimate the immediate adhesive performance of more technique-sensitive dentin bonding systems. The impact of intrapulpal pressure on bond strength seems to be more adhesive dependent than dentin morphological characteristics related to depth. (C) 2007 Wiley Periodicals, Inc.
Keywords: bond strength; dentin; bonding agents; intrapulpal pressure; dentin depth